Meningkatkan Literasi Dan Numerasi Pada Anak di SD 130 Inpres Gantarang - Wahyu Muh. Syata; Bellona Mardatillah Sabillah; Ramlah Ramadhani.Ns (Yayasan Habiburrahman Jamalu Bina Ummat, 2024)
This community service activity is aimed at elementary school children. This project is centered on the implementation of the Teaching Campus program, with work programs in the form of learning activities such as increasing literacy and numeracy, as well as establishing private classrooms. This activity will last for four months, from August to December 2023. Students are assisted with the following activities: (1) initial observation; (2) implementation stage, which includes assisting teaching and learning activities and leading individual classes. (3) The assessment stage of this work program will be able to have a positive influence on these children by developing new abilities, a love of learning, and a learning mindset, therefore this work program activity is carried out with the agreement of partners. These children receive instruction in reading and arithmetic. Children also practice what they have learned so they can explain it to others in a way that makes sense to them. In order to develop into a person who is not shy about communicating his understanding, this is used to build his self-confidence.